2016
DOI: 10.3126/jonmc.v5i2.16310
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Torch Profile in First Trimester Spontaneous Miscarriage

Abstract: Background TORCH is a group of organisms like Toxoplasma, Rubella, Cytomegalo virus and Herpes simplex virus. These groups of organisms causing infections in pregnant lady leads to various degree of adverse pregnancy outcomes in the form of spontaneous abortion, preterm delivery, intrauterine growth restriction, severe congenital defect with syndromic babies. So, to observe the relationship of TORCH infection in first trimester spontaneous miscarriage in our population and to treat them, this study was perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 9 publications
1
3
0
Order By: Relevance
“…The IgM seroprevalence in the current study is comparable to 1/352 (0.3%) found by Onadeko et al [22]. It is, however, lower than 7.6%, 8.9%, 11.7% by Deji-Agboola et al Nasir et al and Lamichhane et al respectively [14,20,35]. This difference may be attributable to the different population studied.…”
Section: Resultssupporting
confidence: 66%
See 1 more Smart Citation
“…The IgM seroprevalence in the current study is comparable to 1/352 (0.3%) found by Onadeko et al [22]. It is, however, lower than 7.6%, 8.9%, 11.7% by Deji-Agboola et al Nasir et al and Lamichhane et al respectively [14,20,35]. This difference may be attributable to the different population studied.…”
Section: Resultssupporting
confidence: 66%
“…The seroprevalence was higher than 12.3% and 17.5% by Xiao et al and Lamichhane et al respectively, who used direct agglutination test [35,36]. The difference in the population studied, and diagnostic technique, may account for the difference in seroprevalence.…”
Section: Resultsmentioning
confidence: 73%
“…Because the developing fetus' immune system is unable to fight off the infectious organism, maternal infections, particularly those that occur early in pregnancy, can cause fetal loss or abnormalities. Numerous investigations have revealed a strong connection between maternal TORCH infections and pregnancy loss [13]. Pregnant women experience a decline in immunity due to changes in their endocrine systems, particularly a weakening of T lymphocyte immunological function, which makes them more vulnerable to contracting TORCH or having the virus reactivate in the future.…”
Section: Discussionmentioning
confidence: 99%
“…A study performed at Nobel Medical College Teaching Hospital by Lamichhane et al [13] revealed that 41.74% were negative and 58.25% were positive for TORCH infections. In contrast to this study, the herpes virus was found to be among the most common causes of first-trimester spontaneous miscarriage in the eastern region of Nepal.…”
Section: Discussionmentioning
confidence: 99%